The Security and Trade Facilitation Nexus : Options for South Asian Countries - Kerswell, Clay (World Bank, Washington, DC, 2015)
Depending on the nature of the threat and the type of transaction and transport, the ability to profile risk and the type of potential risk-mitigation intervention will be different. If the predominant risk is economic (undervaluation, for instance), a certain set of transactional data can help profile and identify high-risk targets. In such cases, physical inspection responses will be not be as effective as conducting post-transaction auditing as the main compliance strategy. Supply-chain security is based on the understanding that industry has an equally strong financial interest in the security and visibility of goods, and is generally better placed to recognize what is normal behavior as goods move through the supply chain. Adoption of a contemporary risk-based regulatory compliance framework vastly improves an institution’s overall ability to ensure security while delivering improved levels of facilitation.